2022
DOI: 10.3390/inorganics10090145
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent Cobalt Complexes with NNS Tridentate Thiosemicarbazones: Preparation, Structural Study and Investigation of Antibacterial Activity and Cytotoxicity against Human Breast Cancer Cells

Abstract: New complexes of trivalent cobalt with substituted thiosemicarbazone ligands having an NNS donor system {HL1 = 4-(4-nitrophenyl)-1-((pyridin-2-yl)methylene)thiosemicarbazide and HL2 = 4-(2,5-dimethoxyphenyl)-1-((pyridin-2-yl)methylene)thiosemicarbazide} were synthesized via the in situ oxidation of divalent cobalt chloride accompanying its addition to the ligands. The complexes C1 and C2 were characterized via elemental (CHNS) analysis and 1H NMR, FT-IR and UV-Vis. spectroscopic data. Further, conductometric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Thiosemicarbazone transition metal complexes are one of the interesting compounds in bioinorganic chemistry field. A large number of transition metal complexes of thiosemicarbazones have been prepared and proven to be of great effectiveness in this respect [1–7] . The biological activities of thiosemicarbazones varies with N (4)‐substituent as well as the ketone or aldehyde from which they were derived.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiosemicarbazone transition metal complexes are one of the interesting compounds in bioinorganic chemistry field. A large number of transition metal complexes of thiosemicarbazones have been prepared and proven to be of great effectiveness in this respect [1–7] . The biological activities of thiosemicarbazones varies with N (4)‐substituent as well as the ketone or aldehyde from which they were derived.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of transition metal complexes of thiosemicarbazones have been prepared and proven to be of great effectiveness in this respect. [1][2][3][4][5][6][7] The biological activities of thiosemicarbazones varies with N(4)-substituent as well as the ketone or aldehyde from which they were derived. It has been reported that an additional chelating site and the presence of alkyl group at the N(4)-position of the thiosemicarbazone moiety greatly enhances biological activity.…”
Section: Introductionmentioning
confidence: 99%